Discovery of Exosomes From Tick Saliva and Salivary Glands Reveals Therapeutic Roles for CXCL12 and IL-8 in Wound Healing at the Tick–Human Skin Interface - Zhou, Wenshuo; Tahir, Faizan; Wang, Joseph Che-Yen; Woodson, Michael; Sherman, Michael B.; Karim, Shahid; Neelakanta, Girish; Sultana, Hameeda (Frontiers in Cell and Developmental Biology, 2020)
Ticks secrete various anti-coagulatory, anti-vasoconstrictory, anti-inflammatory, and anti-platelet-aggregation factors in its saliva at the bite site during feeding to evade host immune surveillance and responses. For the first time, we report successful isolation of exosomes (small membrane bound extracellular signaling vesicles) from partially fed or unfed Ixodidae tick saliva, and salivary glands, ISE6 cell line and show their novel role in the inhibition of wound healing via CXCL12 and IL-8. Cryo-EM analysis revealed that tick saliva and salivary glands are composed of heterogeneous population of in vivo exosomes with sizes ranging from 30-200 nm. Enriched amounts of tick CD63 ortholog protein and HSP70 were evident in these exosomes. Treatment of human skin keratinocytes (HaCaT cells) with exosomes derived from tick saliva/salivary glands or ISE6 cells dramatically delayed wound healing and repair process. Cytokine array profiling followed by immunoblotting and quantitative-PCR analysis revealed that HaCaT cells treated with exosomes-derived from tick saliva/salivary glands or ISE6 cells showed enhanced IL-8 levels and reduced CXCL12 levels. Inhibition of IL-8 or CXCL2 further delayed exosome-mediated wound healing and repair process, suggesting a skin barrier protection role for these chemokines at the tick bite site. In contrast, exogenous treatment of CXCL12 completely restored this delay and enhanced repair process. Taken together, our study provides novel insights on how tick salivary exosomes secreted in saliva can delay wound healing at the bite site to allow, ease and facilitate successful blood feeding at the tick bite site.